Spiroplasma eriocheiris Invasion Into Macrobrachium rosenbergii Hemocytes Is Mediated by Pathogen Enolase and Host Lipopolysaccharide and β-1, 3-Glucan Binding Protein - Ning, Mingxiao; Xiu, Yunji; Yuan, Meijun; Bi, Jingxiu; Hou, Libo; Gu, Wei; Wang, Wen; Meng, Qingguo (Frontiers in Immunology, 2019)
Spiroplasma eriocheiris is a crustacean pathogen, without a cell wall, that causes enormous economic loss. Macrobrachium rosenbergii hemocytes are the major targets during S. eriocheiris infection. As wall-less bacteria, S. eriocheiris, its membrane protein should interact with host membrane protein directly and firstly when invaded in host cell. In this investigation, six potential hemocyte receptor proteins were identified firstly that mediate interaction between S. eriocheiris and M. rosenbergii. Among these proteins, lipopolysaccharide and β-1, 3-glucan binding protein (MrLGBP) demonstrated to bind to S. eriocheiris using bacterial binding assays and confocal microscopy. Four spiroplasma ligand proteins for MrLGBP were isolated and identified. But, competitive assessment demonstrated that only enolase of S. eriocheiris (SeEnolase) could be a candidate ligand for MrLGBP. Subsequently, the interaction between MrLGBP and SeEnolase was confirmed by co-immunoprecipitation and co-localization in vitro. After the interaction between MrLGBP and SeEnolase was inhibited by antibody neutralization test, the virulence ability of S. eriocheiris was effectively reduced. The quantity of S. eriocheiris decreased in Drosophila S2 cells after overexpression of MrLGBP, compared with the controls. In addition, RNAi knockdown of MrLGBP made M. rosenbergii more sensitive to S. eriocheiris infection. Further studies found that the immune genes, including MrLGBP and prophenoloxidase (MrproPO), MrRab7A and Mrintegrin α1 were significantly up-regulated by SeEnolase stimulation. After SeEnolase pre-stimulation, the ability of M. rosenbergii resistance to S. eriocheiris was significantly improved. Collectively, this investigation demonstrated that MrLGBP and pathogen SeEnolase involved in mediating S. eriocheiris invasion into M. rosenbergii hemocytes.